2004
DOI: 10.1073/pnas.0400035101
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Smad7 expression by ubiquitin-dependent degradation contributes to renal fibrosis in obstructive nephropathy in mice

Abstract: Overexpression of transforming growth factor ␤ (TGF-␤) has been shown to play pathogenic roles in progression of renal fibrosis, and the severity of tubulointerstitial fibrosis correlates better with renal function than the severity of glomerulosclerosis. Smad proteins are signaling transducers downstream from TGF-␤ receptors. Three families of Smad proteins have been identified: receptorregulated Smad2 and Smad3, common partner Smad4, and inhibitory Smad7 (part of a negative-feedback loop). We investigated Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
209
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(217 citation statements)
references
References 28 publications
6
209
0
2
Order By: Relevance
“…Recent reports indicate that Smad7 is selectively decreased, whereas phosphorylation of Smad2 and Smad3 is increased in UUO model. 12 Furthermore, it has been previously shown in several different cell lines that microtubules serve as negative regulator for TGF-b/Smad signaling by forming a complex with endogenous Smad2, Smad3 and Smad4, thus sequestering the R-Smads away from the TGF-b receptor. 11 Therefore, it is conceivable that stabilization of microtubules by low-dose paclitaxel can dampen the exacerbated TGF-b signaling as reported in TGF-b-induced inhibition of myogenesis in C2C12 myoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports indicate that Smad7 is selectively decreased, whereas phosphorylation of Smad2 and Smad3 is increased in UUO model. 12 Furthermore, it has been previously shown in several different cell lines that microtubules serve as negative regulator for TGF-b/Smad signaling by forming a complex with endogenous Smad2, Smad3 and Smad4, thus sequestering the R-Smads away from the TGF-b receptor. 11 Therefore, it is conceivable that stabilization of microtubules by low-dose paclitaxel can dampen the exacerbated TGF-b signaling as reported in TGF-b-induced inhibition of myogenesis in C2C12 myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…11 Also, there are certain literature reports that indicate aberrant ECM deposition in unilateral ureteral obstruction (UUO) model may be due to selective decrease of inhibitory Smad7 and increase of R-Smad3. 12 The aim of this study was to assess if microtubule stabilization with low-dose paclitaxel (Taxol) could inhibit TGF-b/Smad signaling and ameliorate renal fibrosis in the UUO model.…”
mentioning
confidence: 99%
“…The high Smad7 levels in pro-inflammatory immune cells from such patients are due to defective ubiquitination and degradation of Smad7 npg that correlates with its enhanced acetylation by p300. In a mouse model of kidney fibrosis the inverse scenario prevails, namely Smad7 levels are very low while Smurf1 and Smurf2 levels and ubiquitination activities are high, which possibly plays causative roles in the progression of renal fibrosis caused by ureteral obstruction [115]. More recent evidence points to Arkadia as the primary mediator of Smad7 downregulation in the fibrotic kidney, a mechanism that also leads to the process of epithelialmesenchymal transition of kidney epithelial cells to contractile myofibroblast-like cells [116,117].…”
Section: Relevance Of Stability Regulation Of Tgfβ Pathway Componentsmentioning
confidence: 99%
“…[11][12][13][19][20][21][22][23] Whereas Fukasawa et al 6,13 reported that Smurf2 mediated the degradation of Smad7, SnoN and Ski in a mouse model of renal tubulointersitial fibrosis, Liu et al 7,24 have shown that the reduction of Smad7 in a rat model of renal tubulointersitial fibrosis and normal human renal tubular epithelial cells may be mainly attributed to Arkadia, but not to Smurf2. Thus, how Arkadia and Smurf2 affect Smad7, SnoN and Ski in organ fibrosis remains to be clarified.…”
mentioning
confidence: 99%
“…3 In the process, negative regulators such as Smad7, SnoN and Ski can downregulate TGF-b signaling through multiple mechanisms. 3,4 Accumulative evidence indicates that the expression of Smad7, SnoN and Ski proteins in some fibrotic models is obviously lower than that in the normal controls, [5][6][7][8][9][10][11][12][13] and also shows that upregulation of the expression of Smad7, SnoN or Ski proteins reverses or blocks fibrogenesis. [14][15][16][17] Nakao et al 18 reported that Smad7 immunoreactivity, which was present mainly in bronchial epithelial cells, was markedly decreased in asthmatic patients, compared with that of control subjects.…”
mentioning
confidence: 99%